The Potential Blockchain Technology in Higher Education Learning Innovations in Era 4.0 - Primasatria Edastama; Suryari Purnama; Riya Widayanti; Lista Meria; Deva Rivelino (IAIC Bangun Bangsa, 2021)
In the world of education, the development of technology systems is increasingly rapid. The implementation of Blockchain continues to be used in various sectors. This study analyzed the use of Blockchain in higher education. The research discussion results lead to the use of blockchain technology, which is a new trend in higher education. Blockchain implementation in higher education creates problems in the use of blockchain technology. Based on the use of Blockchain in research, we are exploring the application of related technologies in higher education. The problem with technology that functions to record small transactions and data used for many sectors such as recording transactions, documentation, and even voting, which is also used in Higher Education, is unfortunately not well implemented. This supports research on the use of blockchain technology that can record transactions in many sectors. Documenting the process of transactions, documentation, and voting can even be used in Higher Education. To improve the blockchain technology system's performance in higher education, it is becoming more effective, efficient, and more accessible in recording transaction processes. It can become a new innovation for Higher Education.